Engineering optimization IV : proceedings of the International Conference on Engineering Optimization (ENGOPT 2014), Lisbon, Portugal, 8-11 September 2014 /: proceedings of the International Conference on Engineering Optimization (ENGOPT 2014), Lisbon, Portugal, 8-11 September 2014. ([2015]) - Unknown
No abstract available